2011
DOI: 10.1111/j.1469-1809.2011.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Syndrome: The FMR1 CGG Repeat Distribution Among World Populations

Abstract: SUMMARY Fragile X Syndrome (FXS) is characterized by moderate to severe intellectual disability which is accompanied by macroorchidism and distinct facial morphology. FXS is caused by the expansion of the CGG trinucleotide repeat in the 5′ untranslated region of the Fragile X mental retardation 1 (FMR1) gene. The syndrome has been studied in ethnically diverse populations around the world and has been extensively characterized in several populations. Similar to other trinucleotide expansion disorders, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 152 publications
4
66
1
4
Order By: Relevance
“…The CGG repeat sizes of 29 and 30 were found to be most common in all ethnic groups, together accounting for 61.1% of the alleles in the cohort and comparable with populations of western European ancestry and other populations in Asia, Indonesia, Brazil, Chile, Cameroon, Ghana and India, and in African Americans. [20] In the present study the 30 CGG repeat (found in 34% of cases) was the most common allele in the white population, which corroborates well with the 39% frequency reported by Goldman. [11] The most common allele in the black population in this study was shown to be 29 CGG repeats (in 41% of the total black cohort).…”
Section: Distribution Of Fmr-1 Allelessupporting
confidence: 81%
“…The CGG repeat sizes of 29 and 30 were found to be most common in all ethnic groups, together accounting for 61.1% of the alleles in the cohort and comparable with populations of western European ancestry and other populations in Asia, Indonesia, Brazil, Chile, Cameroon, Ghana and India, and in African Americans. [20] In the present study the 30 CGG repeat (found in 34% of cases) was the most common allele in the white population, which corroborates well with the 39% frequency reported by Goldman. [11] The most common allele in the black population in this study was shown to be 29 CGG repeats (in 41% of the total black cohort).…”
Section: Distribution Of Fmr-1 Allelessupporting
confidence: 81%
“…8 The present study was aimed at comparing the distribution of FMR1 genotypes between BRCA mutation carriers and non-carriers in a cohort of Italian women, free of cancer or affected by breast and/ or ovarian cancer, who were tested for the presence of BRCA mutation in a clinical setting because of their personal and/or familial cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…While the distribution of CGG repeat total length has been reported in a number of populations (27), fewer studies have reported the distribution of AGG interruptions within populations. This study reports on the AGG interruption patterns in a total of 3,065 normal alleles (9-40 CGG repeats) from 1,989 participants (males: n = 794; females: n = 1,195) from 9 countries: Australia, Chile, Emirates, Guatemala, Indonesia, Italy, Mexico, Spain, and USA.…”
Section: Introductionmentioning
confidence: 99%